Application of the balanced scorecard in an emergency department of a regional hospital in Morocco - Abdelhaq, FLILISS; Tarik, JELLOULI (Journal of Neonatal Surgery, 2025)
This research aims to evaluate the effectiveness of an emergency department in Morocco using a customised Balanced Scorecard (BSC). Given the challenges faced in today's hospital environment, such as an ageing population and budgetary constraints, this study highlights key indicators that encompass the financial, customer, process and learning domains. The data is collected using a mixed method approach. The results highlight the importance of more effective data management and accumulated staff involvement in achieving sustainable performance. The aim of the optimised Balanced Scorecard is to improve both operational efficiency and patient satisfaction. Successful implementation relies on effective data management and staff engagement.